2019
DOI: 10.3390/ma12071025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Material Properties of Carbon Fiber Reinforced Polymer (CFRP) Tendons: Experiments and Model Assessment

Abstract: Material properties at elevated temperatures are important factors in the fire safety design and numerical analysis of concrete members strengthened with fiber reinforced polymer (FRP) composites. Most of the previous research mainly focused on tensile strength and elastic modulus in conventional steady state temperature tests. However, the transient state test method is more realistic for strengthening concrete structures. At the same time, the coefficient of thermal expansion of FRP composites is also one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 21 publications
2
53
0
1
Order By: Relevance
“…Comparatively little information is currently available on the degradation of mechanical properties and damage mechanisms of heat-exposed UD CFRP specimens in the form of either coupons, rods, strips, or tendons under tension [ 28 , 29 , 30 , 31 ]. Feih and Mouritz [ 28 ] investigated the tensile strength and fiber modulus of pure PAN-based T700 fibers and found that the fibers retained 50% of their room temperature UTS when exposed to temperatures between 400 and 600 °C in air.…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively little information is currently available on the degradation of mechanical properties and damage mechanisms of heat-exposed UD CFRP specimens in the form of either coupons, rods, strips, or tendons under tension [ 28 , 29 , 30 , 31 ]. Feih and Mouritz [ 28 ] investigated the tensile strength and fiber modulus of pure PAN-based T700 fibers and found that the fibers retained 50% of their room temperature UTS when exposed to temperatures between 400 and 600 °C in air.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the development of FRP composite materials is accompanied by many challenges that must be seriously considered to achieve more extensive application of FRP materials in the construction fields. One of these challenges concerns understanding the performance of FRP materials when exposed to high temperature [6][7][8][9]. This is because once the glass transition temperature (T g ) of the epoxy matrix is approached, most FRP materials display a significant reduction of strength, stiffness, and bonding characteristics at even moderate temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the obtained principal stresses and strains is high for elevated temperatures [21,22,31]. The stresses and strains are found to be intense along the x-y plane, and minimal along at z-x plane, and thus elastic deformation is higher along this plane.…”
Section: Thermo-elastic Deformation At Low Beam Powermentioning
confidence: 84%